2011
DOI: 10.1126/science.1204963
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence of Murine-Like Gammaretroviruses in CFS Patients Previously Identified as XMRV-Infected

Abstract: *Members of the gammaretroviruses-such as murine leukemia viruses (MLVs), most notably XMRV [xenotropic murine leukemia virus (X-MLV)-related virus-have been reported to be present in the blood of patients with chronic fatigue syndrome (CFS). We evaluated blood samples from 61 patients with CFS from a single clinical practice, 43 of whom had previously been identified as XMRV-positive. Our analysis included polymerase chain reaction and reverse transcription polymerase chain reaction procedures for detection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
115
1
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(125 citation statements)
references
References 30 publications
8
115
1
1
Order By: Relevance
“…XMRV was also reported to be presence in patients with chronic fatigue syndrome (CFS) (Lombardi et al, 2009). However, the link between XMRV and CFS is unclear, because in other studies it has failed to detect XMRV infection in CFS patients Groom et al, 2010;Switzer et al, 2010;van Kuppeveld et al, 2010;Knox et al, 2011;Satterfield et al, 2011;Shin et al, 2011). However, gammaretroviruses are known to induce cancer in animals, understanding XMRV or related MLV infections in human prostate cancer tissues will shed light on their potential contribution to human disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…XMRV was also reported to be presence in patients with chronic fatigue syndrome (CFS) (Lombardi et al, 2009). However, the link between XMRV and CFS is unclear, because in other studies it has failed to detect XMRV infection in CFS patients Groom et al, 2010;Switzer et al, 2010;van Kuppeveld et al, 2010;Knox et al, 2011;Satterfield et al, 2011;Shin et al, 2011). However, gammaretroviruses are known to induce cancer in animals, understanding XMRV or related MLV infections in human prostate cancer tissues will shed light on their potential contribution to human disease.…”
Section: Introductionmentioning
confidence: 99%
“…Proposed reasons to explain the conflicting data are unknown but may be: technical differences, lack of standardized XMRV PCR assays, assay sensitivity, contamination by and cross-reactivity of XMRV PCR assays with closely related endogenous MLVs such as trace quantities of mouse genomic DNA found in reagents and samples (Hue et al, 2010;Oakes et al, 2010;Robinson et al, 2010;Sato et al, 2010;Knox, Carrigan et al, 2011;Tuke et al, 2011), differences in the geographical distribution of XMRV, sequence differences among XMRV genomes (Silverman et al, 2010;Singh et al, 2010;Knox et al, 2011) and factors related to the population genetic factors (Switzer et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In der Mehrzahl der später veröffentlich-ten Studien wurde XMRV jedoch in keiner einzigen Probe nachgewiesen [8,9,10,11,12,13]. Bei Wiederholungsuntersuchungen von zuvor am WPI im Rahmen der initialen Studie [3] positiv getesteten CFS-Patienten konnten in unabhängigen Laboren in keinem einzigen Fall XMRV oder spezifische Antikörper gegen XMRV-Proteine nachgewiesen werden, obwohl nahezu identische, hochsensitive Verfahren verwendet wurden [14,15]. Hiermit stellt sich die Frage, was die Ursache für den beschriebenen Nachweis von XMRV am WPI und an einem kommerziellen Labor sowie in den anderen Studien sein könnte.…”
Section: Ursprüngliche Einschätzung Von Xmrv Als Neues Retrovirus Mitunclassified
“…Furthermore, XMRV may be the result of a recombination of two MLV ancestors in laboratories (16). In addition to the negative findings in CFS patients (17,18), it was demonstrated that there is no evidence of XMRV infection in blood donors in the USA (19). In Japan, Furuta et al did not detect XMRV in CFS patients (8).…”
mentioning
confidence: 90%